Naturalistic decision making in high performance team sport coaching - Harvey, S.; Baird Lyle, J. W.; Muir, B. (International Sport Coaching Journal, 2015)
A defining element of coaching expertise is characterised by the coach`s ability to make decisions. Recent literature has explored the potential of Naturalistic Decision Making (NDM) as a useful framework for research into coaches` in situ decision making behaviour. The purpose of this paper was to investigate whether the NDM paradigm offered a valid mechanism for exploring three high performance coaches` decision-making behaviour in competition and training settings. The approach comprised three phases: 1) existing literature was synthesised to develop a conceptual framework of decision-making cues to guide and shape the exploration of empirical data; 2) data were generated from stimulated recall procedures to populate the framework; 3) existing theory was combined with empirical evidence to generate a set of concepts that offer explanations for the coaches` decision-making behaviour. Findings revealed that NDM offered a suitable framework to apply to coaches` decision-making behaviour. This behaviour was guided by the emergence of a slow, interactive script that evolves through a process of pattern recognition and/or problem framing. This revealed `key attractors` that formed the initial catalyst and the potential necessity for the coach to make a decision through the breaching of a `threshold`. These were the critical factors for coaches` interventions.